Hubungan Profesionalitas dan Motivasi Kerja Dengan Produktivitas Kinerja Guru Sekolah Dasar di Kecamatan Palu Timur - Hartati Is Mentemas; Andi Tanra Tellu; Suherman Suherman (Universitas Tadulako, 2019)
This research aimed to describe and to analyze effect the profesional ity and work motivation with performance of elementary school teachers in Palu Timur. The research is quantitative research used survey method on distributed 571 teachers in Palu Timur. The sample teachers were 142 persons. The research data were collected by using a questionnaire and analyzed by SPSS 14.0 version and MS Excel. Based on the analyses: (1) there is a significant effect between profesional ity and performance; (2) there is a significant effect between work motivation and performance; and (3) there is a significant effect between profesional ity and work motivation together with work performance of the elementary school teachers at Palu Timur.